2019
DOI: 10.3390/app9194116
|View full text |Cite
|
Sign up to set email alerts
|

Electricity Evaluation and Emission Characteristics of Poultry Litter Co-Combustion Process

Abstract: Electricity generation and emission characteristics during the poultry litter and natural gas co-combustion process has rarely been studied. In this study, a Stirling engine was successfully integrated into the existing lab-scale swirling fluidized bed combustion system in order to further investigate the poultry litter and natural gas co-combustion process. Electricity, gaseous emissions, particulate matter (PM), and fly ash composition were analyzed under various operating conditions. Results indicated that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
53
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(54 citation statements)
references
References 28 publications
1
53
0
Order By: Relevance
“…Ammonia (NH 3 ) emissions originating from poultry litter account for 27% of the total atmospheric NH 3 emissions in the United States [1]. The United States produces approximately 12.6 tons of poultry litter every year, assuming 1.4 tons of litter is produced per 1,000 birds [2,3]. Moore et al [4] estimated the total NH 3 loss from poultry production to be 46 g NH 3 per broiler.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ammonia (NH 3 ) emissions originating from poultry litter account for 27% of the total atmospheric NH 3 emissions in the United States [1]. The United States produces approximately 12.6 tons of poultry litter every year, assuming 1.4 tons of litter is produced per 1,000 birds [2,3]. Moore et al [4] estimated the total NH 3 loss from poultry production to be 46 g NH 3 per broiler.…”
Section: Introductionmentioning
confidence: 99%
“…Recent research investigating the combustion process of poultry litter has found that combusting biomass waste (poultry litter) with fossil fuels (coal, natural gas etc.) known as co-combustion, can reduce emissions [2,28,29].…”
Section: Introductionmentioning
confidence: 99%
“…For example, between the heater -expansion spaces, during the flow from the expansion space the temperature is lower, and during the flow from the heater, the temperature is higher and corresponds to that in the heater. On this basis, the adiabatic work has been calculated (19) and, after taking pumping loss (22) into account the net adiabatic work (23) has been also calculated. For further considerations regarding the impact of selected design features of the system on the efficiency and power, the authors decided to use the simplified characteristics of the regenerator effectiveness taking into account only the effect of charge pressure:…”
Section: Resultsmentioning
confidence: 99%
“…The net adiabatic work corresponding to indicated work, is a difference of the work calculated for the evaluated pressure change (19) and the pumping loss (22):…”
Section: Of 21mentioning
confidence: 99%
See 1 more Smart Citation